Trades boards as a means of adjusting wages disputes and promoting trade interests - O'Connell, John Robert (Statistical and Social Inquiry Society of Ireland, 1919)
In a time like the present, when the differences between Capital and Labour appear to be more than ordinarily acute, it seems opportune to invite the attention of this Society to those Acts of Parliament, some of which have now been in force for some ten years, which seem to suggest the possibility of one method of drawing closer together those whose interest in an industry is that of an employer and those whose interest is that of a worker. So far as I am aware, this Society has up to the present not had under its consideration the Trade Boards Act, 1909 (9 Edwd. VII., Ch. 22), the Trade Boards Provisional Orders Confirmation Act, 1913 (3 & 4 Geo. V., Ch. 67). or the Trade Boards Act, 1918 (8 & 9 George: V., Ch. 32), which constitute a code of legislation designed to obviate trade disputes in respect of wages by setting up Boards consisting partly of representatives of employers and partly of representatives of workers, together with certain independent persons appointed by the Ministry of Labour, who are empowered to fix minimum wages for all persons employed in the various trades to which the Acts apply.
Read May 30th, 1919,
Keywords: Trade unions; Minimum wage; 314.15